Gluten-free tarhana fortified with different ratios of edible mushroom Lactarius deliciosus - Süfer, Ö. (2024)
The present work aimed to develop nutritious and delicious tarhana soup for people who are especially sensitive to gluten. An edible mushroom, Lactarius deliciosus, was used in the gluten-free soup formulation instead of rice flour with different fortification ratios (0, 25, 50, 75, and 100%). Crude ash, crude protein, crude fat, mineral, acidity, water and oil absorptions, total phenolics, and antioxidant activities of gluten-free tarhana samples increased with the fortification of L. deliciosus in a dose-dependent manner, though the samples lost their lightness (L*), hue angle (H°), and chroma (C*) values. Total carbohydrate was calculated by subtracting the sum of crude ash, crude protein, and crude fat contents, and determined in the range of 64.31 - 78.51%. Potassium was the most abundant mineral found in samples, followed by calcium, and magnesium. Total polyphenols increased to 14,847.28 from 1,526.46 mg/kg gallic acid equivalent (GAE) for 100% fortification of L. deliciosus powder on dry weight basis (DWB). Antioxidant activity by ferric reducing antioxidant power (FRAP) assay (3.01 - 10.14 mmol Trolox equivalent, TE/kg DWB) was comparably higher than that with the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay (1.09 - 8.81 mmol TE/kg DWB). Gluten-free tarhana sample fortified with 25% L. deliciosus powder (DWB) had the highest sensory scores with respect to colour, taste, mouthfeel, and overall acceptability.